2021
DOI: 10.1093/rheumatology/keab611
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and peculiar immunological manifestations of SARS-CoV-2 infection in systemic lupus erythematosus patients

Abstract: Objectives The impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in patients with systemic lupus erythematosus (SLE) remains unclear and data on clinical manifestations after infection are lacking. The aim of this multicentre study is to describe the effect of SARS-CoV-2 in SLE patients. Methods SLE patients referring to 4 Italian centres were monitored between February 2020 and March 2021. All patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…As shown above, the vaccine showed no direct association with flare, while SARS-CoV-2 infection was reported as an independent risk factor for RD flare in some studies ( 52 54 ). The flare rate of RD after SARS-CoV-2 infection presented a vastly higher flare risk than that after vaccination ( 52 58 ), with most flare rates being higher than 20% and some even higher than 40%. This may also encourage RD patients to receive the COVID-19 vaccination.…”
Section: The Flare Risk After Sars-cov-2 Infection Compared To the Fl...mentioning
confidence: 91%
“…As shown above, the vaccine showed no direct association with flare, while SARS-CoV-2 infection was reported as an independent risk factor for RD flare in some studies ( 52 54 ). The flare rate of RD after SARS-CoV-2 infection presented a vastly higher flare risk than that after vaccination ( 52 58 ), with most flare rates being higher than 20% and some even higher than 40%. This may also encourage RD patients to receive the COVID-19 vaccination.…”
Section: The Flare Risk After Sars-cov-2 Infection Compared To the Fl...mentioning
confidence: 91%
“…Although patients with ADs -SLE within this group- have a higher prevalence of COVID-19 [ 25 ], there are some cohort studies which have shown no increase in SARS-CoV-2 risk of infection in these patients [ 26 ]. Studies reported an increased mortality rate in the patients with systemic autoimmune rheumatic diseases compared to the general population [ 27 ]; but this increase has not yet been determined whether it is solely due to COVID-19, or the delayed diagnosis and treatment of their pre-existing systemic autoimmune rheumatic diseases [ 28 ].…”
Section: Common Autoimmune Diseasesmentioning
confidence: 99%
“…The most common SARS-CoV-2 clinical manifestations in lupus patients are fever, anosmia and cough [ 26 ]. Patients with pre-existing lupus disease may have flares during the course of COVID-19, including worsening or different clinical signs, manifestations, and laboratory parameters indicating involvement of one or more organs [ 33 , 34 ].…”
Section: Common Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although data are limited, a SARS-CoV-2 infection might trigger increased disease activity of the underlying IMID. [8][9][10][11] In this study we aimed to investigate long-term humoral immune responses and changes in disease activity after a polymerase chain reaction (PCR) or antigen test proven primary SARS-CoV-2 infection in unvaccinated IMID patients using different types of ISPs.…”
Section: Introductionmentioning
confidence: 99%